Preparation of Silver Nanoparticle and Its Application to the Determination of ct-DNA - Liu, Chunhua (Molecular Diversity Preservation International (MDPI), 2007)
new method to prepare silver nanoparticles was reported in this paper, which based on aqueous-gaseous phase reaction of silver nitrate solution and ammonia gas. The proposed method is effective, rapid, and convenient. Transmission electron microscope (TEM) and X-ray diffraction (XRD) were used to characterize the structure of the particles, respectively. It was found that the average diameter of the particles was about 10 nm and the shape was spherical. And the strong fluorescence signal of the silver nanoparticles solution can be quenched after the adding of the calf thymus DNA (ct-DNA) solution. The quenched fluorescence intensity was linear with the concentration of ct-DNA in the range of 0.5 to 5.0 × 10(4) ng mL(-1) with a detection limit of 0.3 ng mL(-1).